The appraisal gap: Why victim and transgressor groups disagree on the need for a collective apology. (7th June 2017) - Hornsey, Matthew J.; Okimoto, Tyler G.; Wenzel, Michael
Abstract: After an intergroup transgression, victims often advocate for a collective apology that the transgressor group is reluctant to provide. We argue that this is partly caused by a discrepancy in the extent to which victim and perpetrator group members appraise transgressions through an intergroup lens. In three experiments, participants read about individuals assaulting members of a racial out‐group. Consistent with predictions, victim group members were more likely than transgressors and third parties to see the events as typical of the transgressor group, more likely to appraise the events as intergroup in nature, and through these processes were more desiring of a collective apology. Transgressors' reluctance to issue a collective apology was not a sign of harm minimization. Indeed, they were more likely than victims to seek an interpersonal apology and less forgiving of the individual transgressors. Cognitive and motivational mechanisms were proposed, although evidence for the latter was limited.